The Effect of Domestic Market Obligation (DMO) Policy on Assurance of Domestic Energy Supply Requirements for Power Generating and National Coal Using Industry - Hadityo Hadityo (Budapest International Research and Critics University, 2022)
Mineral and coal mining is one of non-renewable natural resources and has an important role to fulfill the lives of many people, therefore, its management, whether the ruling system, implementation, supervision and evaluation shall be well accounted for. It is hoped that the blessing of God Almighty could have a value added upon the economic development, create job fields, empower communities, and other multiplier effects. This writing discussed three main points, that are (1) how to regulate energy management in Indonesia in order to meet the domestic needs; (2) how is the national coal mining reserve and resources situation; (3) how is the realization of the Domestic Market Obligation policy in Indonesia. The research method used in this writing is normative legal research method. The analytic method used is qualitative and specified in descriptive research.The research concludes that the concept of establishing the current Domestic Market Obligation policy needs to be reexamined as a government legal policy that its main objective to optimize domestic demand without harming the industrial sector which also implies an increase in electricity rates.